Completion of Circle Material Problems Using the Jumping Task Approach to Junior High School Students - Rahma, Nadya Alvi; Sari, Nissa Kurnia (Syiah Kuala University, 2023)
In order to practice critical thinking skills, it is necessary to get used to practicing questions such as questions based on jumping tasks. The jumping task question is a question with a level of difficulty above the curriculum. In solving math problems based on jumping tasks, students often face obstacles. This study aims to describe the profile of students' critical thinking towards solving mathematical problems based on jumping tasks on circle material. The research was conducted at MTsN 2 Blitar with 2 students each having adversity quotient types of climber, camper, and quitter. The data collection technique used was an adversity response profile questionnaire, a jumping task-based math problem solving test and interviews. The research results obtained showed that at the stage of understanding the problem both climber, camper and quitter subjects were able to show interpretation after reading the questions. However, the quitter subject is less precise in interpreting important information from the problem. In the problem-solving planning stage, the plan presented by the climber subject was more appropriate than the plan presented by the camper subject, while the quitter subject was unable to develop a settlement plan and the work process stopped at this stage.